2013
DOI: 10.1270/jsbbs.63.339
|View full text |Cite
|
Sign up to set email alerts
|

Detection and verification of QTLs associated with heat-induced quality decline of rice (<i>Oryza sativa</i> L.) using recombinant inbred lines and near-isogenic lines

Abstract: Decline in the apparent quality of rice (Oryza sativa L.) grain due to high temperatures during ripening recently became a major concern in many areas in Japan. The occurrence of white-back kernels (WBK) is one of the main problems of heat-induced quality decline. We identified QTLs associated with the occurrence of WBK using recombinant inbred lines (RILs) and verified their effects using near-isogenic lines (NILs). The QTL analysis used F7 and F8 RILs derived from ‘Hana-echizen’ (HE), which is tolerant to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…Based on the regularity of starch accumulation as described in the above section (Nagato & Kobayashi, 1959), the appearance of dehulled grains can be objectively evaluated using a chalky rice grain predictor that is capable of determining the number of milky-white grains effects of QTLs for white-back grain using near-isogenic lines (Kobayashi et al, 2013;Wada et al 2015). These findings will accelerate development of heat-tolerant variety to decrease white-back and basal-white grains under high temperature.…”
Section: Countermeasures Against Heat Damage Focusing On Each Type Ofmentioning
confidence: 99%
“…Based on the regularity of starch accumulation as described in the above section (Nagato & Kobayashi, 1959), the appearance of dehulled grains can be objectively evaluated using a chalky rice grain predictor that is capable of determining the number of milky-white grains effects of QTLs for white-back grain using near-isogenic lines (Kobayashi et al, 2013;Wada et al 2015). These findings will accelerate development of heat-tolerant variety to decrease white-back and basal-white grains under high temperature.…”
Section: Countermeasures Against Heat Damage Focusing On Each Type Ofmentioning
confidence: 99%
“…Microscopic observation showed that chalking occurs at the belly, back, base, or center parts of the grains. Although highly effective quantitative trait loci (qWB6, qWB9) associated with the occurrence of white-back kernels have been identified (Kobayashi et al, 2013), the precise mechanism controlling the localization of chalking remains unclear. The imbalance of starch biosynthesis and degradation might be generated by the spatial expression of the genes responsible.…”
Section: Perspectivementioning
confidence: 99%
“…Kobayashi et al (2007) detected three QTLs on chromosomes 3, 4, and 6 using F 2 and F 3 populations derived from a cross between Hana-echizen and niigatawase. An nIL carrying a QTL on chromosome 6 (qWB6) introduced from Hana-echizen into the niigatawase background was developed (Kobayashi et al, 2013). This nIL carrying qWB6 significantly decreased WBCG at 27.3-31.1 °C during grain filling.…”
Section: Genetic Analysis For Wbcgmentioning
confidence: 99%
“…This nIL carrying qWB6 significantly decreased WBCG at 27.3-31.1 °C during grain filling. In addition to qWB6, Kobayashi et al (2013) Gene profiling by comprehensive expression analyses could be useful to narrow down the candidate genes in high-resolution linkage mapping for WBCG.…”
Section: Genetic Analysis For Wbcgmentioning
confidence: 99%